RT-TDDFT study of hole oscillations in B-DNA monomers and dimers - Tassi, M.; Morphis, A.; Lambropoulos, K.; Simserides, C. (Cogent Physics, 2017)
AbstractWe employ Real-Time Time-Dependent Density Functional Theory to study hole oscillations within a B-DNA monomer (one base pair) or dimer (two base pairs). Placing the hole initially at any of the bases which make up a base pair, results in THz oscillations, albeit of negligible amplitude. Placing the hole initially at any of the base pairs which make up a dimer is more interesting: For dimers made of identical monomers, we predict oscillations with frequencies in the range f≈ 20–40 THz, with a maximum transfer percentage close to 1. For dimers made of different monomers, f≈ 80–400 THz, but with very small or small maximum transfer percentage. We compare our results with those obtained recently via our Tight-Binding approaches and find that they are in good agreement.